The systematic status of Gonocephalus robinsonii Boulenger, 1908 (Squamata: Agamidae: Draconinae) - Denzer, Wolfgang; Manthey, Ulrich; Mahlow, Kristin; Böhme, Wolfgang (Zootaxa, 2015)
The generic assignment of the draconine lizard Gonocephalus robinsonii from the highlands of West-Malaysia has been uncertain since the original description. Here we present a study based on morphology, previously published karyotype data and molecular phylogenetics using 16S rRNA sequences to evaluate the systematic status of G. robinsonii. As a result we describe Malayodracon gen. nov. to accommodate the species.